2022
DOI: 10.1039/d2ob01646j
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalyzed double Cvinyl–H bond activation: synthesis of conjugated dienes

Abstract: Conjugated dienes occupied a pivotal position in the field of synthetic organic chemistry and medicinal chemistry. They act as important synthons for the synthesis of various biologically important molecules and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 162 publications
1
9
0
Order By: Relevance
“…Regarding the palladium source, in agreement with the literature, [3] palladium halides lead to modest conversions (Table 3, runs 8-9), as well as palladium in the zero-oxidation state (table 3, run 10). In this regard, it was observed that starting with Pd(0), the conversions in the first hour of the reaction are very low, suggesting the need for an induction time required for the oxidation of palladium before it can be catalytically active.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Regarding the palladium source, in agreement with the literature, [3] palladium halides lead to modest conversions (Table 3, runs 8-9), as well as palladium in the zero-oxidation state (table 3, run 10). In this regard, it was observed that starting with Pd(0), the conversions in the first hour of the reaction are very low, suggesting the need for an induction time required for the oxidation of palladium before it can be catalytically active.…”
Section: Resultssupporting
confidence: 85%
“…The oxidation or acetoxylation of the olefin, as well as its non‐oxidative dimerization, are competitive processes, and in the presence of arenes, the olefin can be also arylated. Reactions are usually carried out in a polar solvent such as water or acetic acid, but also classic organic solvents and both homogeneous and heterogeneous palladium catalysts (recently also other metals) are known [1–3,7,8,12,14,15] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these structural motifs also play important roles in organic synthesis and materials science, such as synthetic intermediates and chelating ligands. Accordingly, considerable efforts have been devoted to developing effective catalytic approaches for the synthesis of such class of compounds, especially stereoselective ones due to the importance of geometry that eventually affects the function. However, while straightforward synthetic strategies now exist for the synthesis of simple 1,3-diene derivatives, acquiring multisubstituted conjugated dienes with readily available starting materials remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Elimination reactions 8 a and olefination reactions 8 b have been widely employed, but they are frequently associated with the problems of uncontrolled generation of E and Z isomers, which need rigorous purification. In the past decades, to realize the stereoselective synthesis of substituted 1,3-dienes, a variety of strategies have been developed, 9 including vinyl C–H bond activation, 9 d cross-coupling reactions, 10 ene-yne metathesis, 11 functionalization of alkynes 12 or 1,3-diynes, 13 isomerization, 14 Kumada vinylation 15 and aerobic dehydrogenation. 16 Despite the effectiveness of the aforementioned methods, developing a direct, highly stereoselective approach towards the synthesis of polysubstituted 1,3-conjugated dienes remains elusive and is highly desirable.…”
mentioning
confidence: 99%